2022
DOI: 10.3390/agronomy12081824
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar on Soil Properties and Tomato Growth

Abstract: The paper aimed at evaluating the effects of biochar (BC) produced by slow pyrolysis of vine pruning residue on soil physicochemical properties and tomato plant growth. A greenhouse experiment was conducted for 66 days, applying different treatments for 3 soil types, i.e., foliar fertilizer, BC (at a volumetric ratio between BC and soil of 20/80), BC + foliar fertilizer, and no treatments. Strongly alkaline BC (pH = 9.89 ± 0.01) had a significant beneficial effect on the growth performance of tomato plants sow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Sial et al (2019) also applied fruit peel biochar to observe their performance in crop growth and he reported enhancement in soil pH, PH and TLCC in wheat. Parallel to the discoveries of our study, Calcan et al (2022) also noticed a significant positive effect of vine pruning residue biochar on some morphological characteristics of tomato including PH, SD, NLP, and volume of root in soil having strong acidity.…”
Section: Effect Of Fruit Peel Biochar Application On the Morphologica...supporting
confidence: 87%
“…Sial et al (2019) also applied fruit peel biochar to observe their performance in crop growth and he reported enhancement in soil pH, PH and TLCC in wheat. Parallel to the discoveries of our study, Calcan et al (2022) also noticed a significant positive effect of vine pruning residue biochar on some morphological characteristics of tomato including PH, SD, NLP, and volume of root in soil having strong acidity.…”
Section: Effect Of Fruit Peel Biochar Application On the Morphologica...supporting
confidence: 87%
“…The favorable impacts of biochar on the physicochemical and biological attributes of the soil collectively enhance the accessibility of essential plant nutrients, typically resulting in enhanced crop performance [27]. Numerous research studies have shown that the application of biochar in combination with both inorganic and organic fertilizers has a positive effect on soil fertility and enhances plant performance [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…This advantage deriving from biochar application can be found in the literature, confirming our results, for example, de la Rosa et al 46 and Schimmelpfennig et al 47 who reported an increased biomass production of up to + 300% and + 50% after application of biochar to grasslands. In a greenhouse experiment on tomato plants, Calcan et al 48 achieved 50% higher values of height, number of leaves, and collar diameter of plants when biochar was added. In the present experiment, inoculation of BBF3 (ABBF3) was characterised by an even higher production than FC, probably due to an increased mobilization of nutrients and the biostimulant effects of the microorganisms applied.…”
Section: Resultsmentioning
confidence: 99%